Neuromodulação do córtex pré-frontal em usuários de crack - Conti, Catarine Lima (2013)
To investigate the electrophysiological effects of the transcranial direct current stimulation (tDCS) applied over the dorsolateral prefrontal cortex (DLPFC) of crack cocaine users, especially during the cognitive potentials N2 and P3 while they are visualizing neutral and crack-related cues. Method: In this randomized, placebo-controlled, parallel group, doubleblinded study, tDCS was performed in twenty abstinent crack-cocaine users (duration of abstinence up to one month) in outpatient care. The patients received either real or sham tDCS for repetitive sessions 9according to the experimental protocol). The primary endpoint was the relapse episodes. Results: Our results demonstrated that the cathodal repetitive tDCS was able to decrease the patients’ brain activity, mainly in the left DLPFC, improving the treatment adherence and decreasing the relapse episodes when compared to sham group and anodal tDCS. Conclusion: Our intervention (the tDCS) showed to be able in modulating the patients’ prefrontal cortex activity, presenting itself as an alternative proposal to the treatment of crack dependence.